2007
DOI: 10.1111/j.1469-8137.2007.02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis reveals interpopulation differentiation and gene flow in the endangered tree Changiostyrax dolichocarpa (Styracaceae) with fragmented distribution in central China

Abstract: Summary• Polymorphic simple sequence repeat (SSR) markers were used to investigate the impact of habitat fragmentation on the population structure and gene flow of Changiostyrax dolichocarpa , a critically endangered tree in central China.• Intrapopulation genetic diversity, population structure and gene flow in the five extant populations of this species were analysed by eight SSR markers.• Intrapopulation genetic diversity results suggest that C . dolichocarpa remnants maintained a relatively high degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 67 publications
2
43
1
1
Order By: Relevance
“…The weak population structure and the non-implication of geographic distances in the genetic differentiation detected in our study are indisagreement with those found by Bakker et al (2009) who revealed a strong populationstructure and a significant isolation by distance in Californian and Eurasian accessions of B.hybridum. Yao et al (2007) suggested that low genetic differentiation and highgene flow between populations can result from long-distance gene dispersal either by pollenor by seeds. Vogel et al (2009) suggested that the predominantly inbreeding system and thesmall hairy seeds, easily dispersed by animals and humans, of the model plant B. distachyonare the most important factors that shape the long seed-mediated gene flow between itsnatural populations and therefore their important role on its genetic structure.…”
Section: Discussionmentioning
confidence: 98%
“…The weak population structure and the non-implication of geographic distances in the genetic differentiation detected in our study are indisagreement with those found by Bakker et al (2009) who revealed a strong populationstructure and a significant isolation by distance in Californian and Eurasian accessions of B.hybridum. Yao et al (2007) suggested that low genetic differentiation and highgene flow between populations can result from long-distance gene dispersal either by pollenor by seeds. Vogel et al (2009) suggested that the predominantly inbreeding system and thesmall hairy seeds, easily dispersed by animals and humans, of the model plant B. distachyonare the most important factors that shape the long seed-mediated gene flow between itsnatural populations and therefore their important role on its genetic structure.…”
Section: Discussionmentioning
confidence: 98%
“…A common misconception about coalescent methods is that because they return information about population history over ''evolutionary'' timescales they have little relevance to ecological questions, which are better answered with other types of analyses based on allele frequency data. Given our emphasis on the intertwined relationships among gene flow, population size, and isolation time, our review did not focus on methods based on genotypic clustering or assignment tests (e.g., Pritchard et al 2000) that can provide estimates of migration rates in recent generations and can be compared to estimates of gene flow from coalescent methods (e.g., Yao et al 2007). Coalescent methods provide time-averaged estimates of demographic parameters only over the temporal scale of the coalescent process for a specific genetic marker, and our analyses of abalone and damselfish data suggest that mtDNA data may often contain too little information for successful application of such methods.…”
Section: Discussionmentioning
confidence: 99%
“…This might be a result of historical population processes, such as natural selection, mutation, isolation and genetic drift (Ming-qian et al 2011;Reed and Frankham 2003). In Changiostyrax dolichocarpa which is pollinated mainly by insects such as bees, genetic diversity using SSR markers revealed that high genetic differentiation and low gene flow between populations can result from short-distance gene dispersal either by pollen or by seed (Yao et al 2007).…”
Section: Discussionmentioning
confidence: 99%